PENERAPAN MODEL PRODUKTIVITAS SMKN BISNIS–MANAJEMEN DI KOTA SEMARANG - Thomas, Partono (Fakultas Ekonomi, Universitas Negeri Semarang, 2013)
The study was inspired by some phenomena such as; the low quality of education in Indonesia, the high unemployment of Vocational high schools graduates and the measurement of school’s productivity which only was seen by the numbers of graduates. The objective of the study was to find the contribution of teachers’ competencies, the culture of school organization, the financing of education, the leadership of the principal, the roles of school committee would influence simultaneously and partially toward the process quality and productivity of vocational high schools based on business-management in Semarang. The respondents were 138 Vocational High Schools teachers based on Business and Management in Semarang. The data were collected by questionnaire, documentation and interview. They were analyzed by doubled regression. The result showed that the culture of organization, the leadership of the principal, and the school committee gave positive influence simultaneously toward the process quality and school productivity. Whereas, the teachers’ competencies and the financing of the school did not give any influence toward the process quality and the school productivity.